2006
DOI: 10.1088/0953-2048/19/3/004
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the microstructural, microchemical and transition temperature gradients of A15 layers in a high-performance Nb3Sn powder-in-tube superconducting strand

Abstract: In the past 5 years there has been a remarkable increase in layer critical current density, J c , for Nb 3 Sn. At ∼5000 A mm −2 (12 T, 4.2 K), the average layer critical current density is now double that of the best ITER central solenoid model coil strand. The improvements in critical current density are a result of increased Sn content in the superconducting A15 phase and better compositional homogeneity, and perhaps other reasons not yet understood. The first indication that such large increases in critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 30 publications
4
24
0
Order By: Relevance
“…Hawes et al [5] find a similar Sn gradient in the SMI PIT wires. Accounting for the ternary composition of the wires #207 and #7069 and for the vs. Sn concentration given in [8], these findings are in agreement with our experimental distributions of .…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Hawes et al [5] find a similar Sn gradient in the SMI PIT wires. Accounting for the ternary composition of the wires #207 and #7069 and for the vs. Sn concentration given in [8], these findings are in agreement with our experimental distributions of .…”
Section: Resultsmentioning
confidence: 71%
“…Long length conductors are now commercially fabricated by three approaches: the Bronze Route, the Internal Sn diffusion process and the Powder-In-Tube (PIT) method [1]. These techniques lead to different thickness of the A15 layer in the filaments, to different compositions and grain morphologies [2]- [5], and to different states of precompression, exerted by the matrix on each filament.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gradient is sensitive to the reaction temperature and duration, and, given a sensible choice for the heat treatment, takes on values of typically 0.1 -0.4 at.%/µm. 5,9,10 Another characteristic feature of PIT Nb 3 Sn wires is their twofold grain morphology: the sub-elements consist of fine grains (∼ 150 nm) on the outside, whereas large grains (∼ 1 -2 µm) dominate near the core. It was found that these two grain types exhibit significantly different T c and B c2 distributions.…”
Section: Introductionmentioning
confidence: 99%
“…The general idea of tube type conductors, where Cu and Sn are inserted into Nb tubes, has been pursued before [7][8][9][10][11], and these conductors do have some similarities to powderin-tube (PIT) strands (as well as differences) [12][13][14][15][16][17][18][19][20][21]. Early on, geometrically similar conductors were fabricated by Murase and associates [7].…”
Section: Introductionmentioning
confidence: 99%